Wayang Beber Pacitan dalam Analisis Struktural - Diah Enggarwati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2016)
Wayang Beber Pacitan as a myth can be seen as a text, which contains signifier and signified. The characters in the puppet is an intermediary for people to interpret the content in Java and basic human traits. Structural analysis Wayang Beber Pacitan bring the following conclusions: First, that the structure of the three are often found in the Java community. Second, that the ideal marriage expected in Pacitan beber wayang stories are cousins once between the two kingdoms (Kediri and Jenggala), although in the Java community does not explicitly recognize their ideal mate. Third, the story Wayang Beber Pacitan is a political story that serves to legitimize the power of the kingdom of Kediri and Janggala. Fourth, that behind the story is that there is a notion of Java: “sopo kang nandur bakal ngundhuh”.